In search of ligands and receptors of the pollen tube: the missing link in pollen tube perception. (20th March 2014) - Hafidh, Said; Potěšil, David; Fíla, Jan; Feciková, Jana; Čapková, Věra; Zdráhal, Zbyněk; Honys, David
Abstract : The journey undertaken by the pollen tube in angiosperms to reach the deeply embedded female gametophyte for fertilization involves persistent guidance by the female gametophyte and accurate perception of the signals by the pollen tube. Several ovule-secreted peptides have been identified. Nevertheless, there are no exact findings on how these signals are perceived by the pollen tube. As a novel approach, we have improvised a modified SIV (semi- in vivo ) technique, SIV-PS (SIV pollen tube secretome), to perform gel-free LC–MS/MS for high-throughput analysis of pollen-tube-secreted proteins. Our approach has led to the identification of over 1400 protein groups. Among them are pollen-tube-secreted ligands and receptor proteins representing potential male components in perceiving ovule-emitted cues for guidance. The present article reviews the missing link in pollen tube perception and showcases the improvised SIV-PS as a tool for high-throughput and targeted study of the pollen tube secretome.